1984
DOI: 10.1017/s0021859600043410
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous and ovarian activities of Finn-cross ewes during the post-partum and the seasonal anoestrous periods

Abstract: SummaryThe seasonal and post-partum oestrus occurrence and ovarian activity, assessed by the plasma progesterone concentrations, were studied in Finn-cross ewes following autumn and winter lambings.The last seasonal oestrous cycle was followed by a silent ovulation in C0% of the Finn × Awassi ewes. Silent ovulations during midanoestrus occurred in 50% of the ewes, and in 90% of the animals a silent ovulation preceded the normal resumption of the seasonal sexual activity.The first post-partum oestrus occurred w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

1985
1985
1991
1991

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…From the results of the present study it appears that after January-February lambings the Finncross ewes of both the control and the light-treated groups resumed normal cycle activity and did not enter seasonal anoestrus, in contrast to previous reports on the same breed (Amir et al 1980;Amir, 1984;Amir, Rosenberg & Schindler, 1984). Still, the mean intervals from lambing to first ovulation and oestrus were considerably longer than those reported after October lambings in the same breed (Amir et al 1984).…”
Section: Discussioncontrasting
confidence: 72%
“…From the results of the present study it appears that after January-February lambings the Finncross ewes of both the control and the light-treated groups resumed normal cycle activity and did not enter seasonal anoestrus, in contrast to previous reports on the same breed (Amir et al 1980;Amir, 1984;Amir, Rosenberg & Schindler, 1984). Still, the mean intervals from lambing to first ovulation and oestrus were considerably longer than those reported after October lambings in the same breed (Amir et al 1984).…”
Section: Discussioncontrasting
confidence: 72%
“…All the ewes of the present work ovulated and the majority of them came into oestrus after lambing. The mean intervals from lambing to first ovulation and oestrus were very similar to those found in ewes of the same breed after October lambing (Amir, Rosenberg & Schindler, 1984), but shorter than the intervals reported after January lambing (Amir & Gacitua, 1985), and do not conform with the absence of oestrous ewes and the occurrence of occasional ovulations only, during this period of the year (Amir et al 1984). It appears, therefore, that in the present study the ewes did not enter seasonal anoestrus after lambing in January-February.…”
Section: Discussionsupporting
confidence: 70%
“…1986), induced an autumn oestrus behaviour in the ewes. The question of the full potential effectiveness of the light and melatonin treatments, alone or in combination, to induce cyclic activity in Finn-cross ewes showing a distinct anoestrous season (Amir et al 1984), remains open.…”
Section: Discussionmentioning
confidence: 99%
“…Silent ovulation seems to be a mediatory step which starts about 1 month before the cessation of ovarian activity. In other studies, silent ovulation was reported to occur before the period of ovarian inactivity (Amir, Rosenberg & Schindler, 1984) or before the ewes entered the breeding season (Mauleon & Dauzier, 1965;Amir et al 1984). Based on the present findings, Rahmani sheep could be considered as a breed with a very long breeding season.…”
Section: Discussionsupporting
confidence: 61%